'The Tsar Gave the Order and the Boyars Assented'. (October 2016) - Nolte, Hans-Heinrich
It is argued that the political institutions of Muscovite Russia (Tsarstvo, adequately translated as kingdom in the early-modern times)—the meeting of the sobor (land) with its three voting bodies and the council of boyars (Duma) on the level of the Tsardom of Russia. As a whole, they were instruments of finding consensus between the Tsar and the powerful and rich groups of the 'country' (Zemlja) such as Church, nobility and big merchants. On the local level, autonomy and cooperation with the center in Moscow was established in the self-government (Mir) of villages and town-quarters (Sloboda), which also organised tax raising and other services for the government as quartering troops. Institutions of local law-enforcement (Guba) cooperated with the Ministry for law enforcement (razbojnik prikaz) in Moscow. Peter I (in the French way, by not convoking the sobor, ending the boyars' council and founding new institutions in a new capital) established absolutism and Empire in Russia. As Putin said, 'Historiography should neither date that change back nor render an image of Russia as immobile and centralistic by nature nor idealize the pre-Petrine system rendering an image of a 'real Russia' back in times.'